Microglial reprogramming: a potential new frontier in enhancing immunotherapy for melanoma brain metastasis - Noam Savion‐Gaiger; Dorin Bar‐Ziv; Harriet Kluger (Molecular Oncology)
The brain is a common site of metastatic dissemination in advanced melanoma. Due to limited access to samples from human brain metastases, our understanding of the tumor microenvironment in the brain lags behind that of other sites, and murine studies are therefore highly informative. Rodriguez‐Baena et al. conducted elegant studies of myeloid cells within melanoma brain metastases, demonstrating their plasticity and changes before and after colonization by melanoma cells. The immune‐inhibitory changes in microglial cells may be reversed or mitigated by inhibition of RelA/NF‐κB.